Repellent effect and protection time of essential oils against the adult stage of Aedes aegypti - Soto-Cáceres, Víctor Alberto (2022)
The aim of this was to evaluate the repellent effect and protection time of essential oils against the adult Aedes aegypti mosquito. A completely randomized design was used with a factorial arrangement that included 10 essential oils (Minthostachys mollis, Schinus molle, Ruta graveolens, Piper aduncun, Myrica pubescens, Lippia alba, Mentha piperita, Lantana glutinosa, Cymbopogon citratus, Eucalyptus globulus and the DEET control. 10%) and four concentrations of the oils (125, 250, 500 and 1000 mg/ml). Each experimental group consisted of 50 adult female A. aegypti mosquitoes raised in the laboratory and the repellent effect and protection time were evaluated using a sedated animal bait (Rattus rattus) with applications of 0.1 ml of the oils on the legs, tail and face. The rats and mosquitoes were found in two communicating cages of 25x25x40 cm. The oils with the greatest repellent effect and protection time, respectively, were C. citratus (97.4%; 165 minutes), E. globulus (95.8%; 165 minutes), L. glutinosa (93.8%; 180 minutes) and M. piperite (93.5%; 180 minutes) in its highest concentration (1000 mg/l); with differences between oils and between concentrations (p<0.001). Likewise, DEET 10% obtained a repellency of 95.3% and a protection time of 173 minutes. It is concluded that the essential oils of C. citratus, E. globulus, L. glutinosa and M. piperita can be considered as having natural repellent potential for A. aegypti.